Predicting Charge Transfer Stability between Sulfide Solid Electrolytes and Li Metal Anodes - Park, Haesun; Yu, Seungho; Siegel, Donald J. (AMER CHEMICAL SOC, 2021)
Reduction or oxidation of a solid electrolyte (SE) by the electrodes of a battery can inject electrons or holes into the SE, inducing unwanted electrical conductivity and/or precipitating harmful interfacial reactions. Here, the likelihood for charge injection from a Li metal anode to 10 sulfide-based SEs is determined by computing the positions of the SE's band edges with respect to the electrochemical potential of the electrode. Although these SEs exhibit large band gaps (>4 eV), nearly all are susceptible to electron injection. One notable exception is the Bcontaining sulfide Li3BS3, which exhibits the greatest resistance to reduction. The trends in charge transfer stability are compared to those for chemical stability with a Li anode and are found to be similar. The combined characterization of chemical and charge transfer phenomena allows for a comprehensive assessment of interfacial stability. The utility of this approach is demonstrated by interpreting recent experiments on the Li/Li2H2PO4/LGPS interface system.
Keywords: LITHIUM BATTERIES; CONDUCTIVITY; LI10GEP2S12; INTERFACES; WINDOW